P070 A retrospective audit of the provision of pepse in a community sexual health clinic. (8th June 2017) - Draeger, Elenor; Vonau, Barbara; Clark, Sarah
Abstract : Introduction: When setting up a specialist GUM clinic within a community sexual and reproductive health service we started offering Post Exposure Prophylaxis (PEPSE) to eligible patients. The patient pathway was to start PEPSE in our service, then attend the HIV clinic in the hospital for all related follow-up appointments. Aims: To audit our practice against the 2011 BHIVA guidelines for the use of PEPSE. Methods: Our electronic record was interrogated for consultations coded as PEPSE between January 2013 and July 2015. 78 records were found, of whom 5 did not receive PEPSE. Thus 72 records were audited. Results: The BHIVA standards were met in all categories that were implemented in the community GUM clinic, but were not met in any of the categories that were implemented in the hospital setting. Discussion: While it is encouraging that PEPSE was initiated successfully in our clinic setting, the follow-up data was disappointing. Following the results of this audit all patients who start on PEPSE in our community clinic are now followed up in the community.